Crotonylation modification and its role in diseases - Guo, Yi; Li, Junqin; Zhang, Kaiming (Frontiers in Molecular Biosciences, 2024)
Protein lysine crotonylation is a novel acylation modification discovered in 2011, which plays a key role in the regulation of various biological processes. Thousands of crotonylation sites have been identified in histone and non-histone proteins over the past decades. Crotonylation is conserved and is regulated by a series of enzymes including “writer”, “eraser”, and “reader”. In recent years, crotonylation has received extensive attention due to its breakthrough progress in reproduction, development and pathogenesis of diseases. Here we brief the crotonylation-related enzyme systems, biological functions, and diseases caused by abnormal crotonylation, which provide new ideas for developing disease intervention and treatment regimens.